Ecological, Social, and Economic-Based Food Security in South Central Timor Regency, East Nusa Tenggara - Hadi Hidayat; Nita Noriko; Taddeo Rusoke (EXSACT-A, 2025)
Stunting is a major public health challenge in Timor Tengah Selatan Regency, East Nusa Tenggara, Indonesia due to ecological limitations and food insecurity that affect child nutritional status. This study analyzes the relationship between environmental carrying capacity, land-use suitability, and local food diversification as strategies to reduce stunting in Pana Village, Kolbano District, East Nusa Tenggara. The results showed that Pana Village experiences ecological constraints, including steep slopes, prolonged dry seasons, limited productive land, and varying soil quality. These conditions reduce agricultural productivity and limiting access to various nutritious food sources, contributing to chronic malnutrition. The study highlights the importance of integrating environmental management with nutrition-based strategies. Recommended interventions include conservation-based agriculture, community micro-irrigation systems, strengthening local institutions capacity, and the development of drought-resistant local crops. This integrated approach is essential to improve food security and child nutrition. This concludes that stunting reduction in Pana Village, Timor Tengah Selatan Regency requires synergy between ecological sustainability, agricultural resilience, and community-based nutrition programs.